Pengembangan Cerita Bergambar Legenda “Lubuk Emas” untuk Mata Pelajaran Membaca A2 - Sherina Olganita Aritonang; Rina Evianty (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The purpose of this research is to create a picture story about the legend of "Lubuk Emas" for Reading A2 class. The creation method was used in this research. The creation process consists of explaining the stages of Richey and Klein's theory. It includes (1) planning, (2) creation, (3) evaluation. The data of this research are the sentences in the folklore "Lubuk Emas". The data source of this research is a book entitled "10 Folk Tales of the Archipelago" by Gamal Komondoko in 2016 with ISBN numbers 979-610-768-6 and 978-979-610-768-1. The result of this research is a picture book "Lubuk Emas" in German. This picture book consists of several pages. The evaluation results show that this picture book has a score of 95 (very good).